2021
DOI: 10.1101/2021.12.09.21267472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural networks for classification and image generation of aging in genetic syndromes

Abstract: In medical genetics, one application of neural networks is the diagnosis of genetic diseases based on images of patient faces. While these applications have been validated in the literature with primarily pediatric subjects, it is not known whether these applications can accurately diagnose patients across a lifespan. We aimed to extend previous works to determine whether age plays a factor in facial diagnosis, as well as to explore other factors that may contribute to the overall diagnosis accuracy. To invest… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…Despite these limitations, one overall interesting conclusion, which echoes some of our previous work, is that a DL model and humans simply perform differently under different circumstances ( Duong et al , 2023 ). As AI tools are adopted in clinical scenarios, better understanding of these differences will be important to ensure that they are useful in helping to diagnose and care for people affected by genetic conditions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Despite these limitations, one overall interesting conclusion, which echoes some of our previous work, is that a DL model and humans simply perform differently under different circumstances ( Duong et al , 2023 ). As AI tools are adopted in clinical scenarios, better understanding of these differences will be important to ensure that they are useful in helping to diagnose and care for people affected by genetic conditions.…”
Section: Discussionsupporting
confidence: 74%
“…After calibration, each participant viewed the 32 images for 7 s per image. We chose 7 s for the viewing time after extensive initial testing and per our previous work using eye-tracking in a related way, as subjective feedback and preliminary assessments showed that this amount of time was sufficient to assess an image but minimized participants visually revisiting areas of the image in a way that might not inform the assessment ( Duong et al , 2023 ).…”
Section: Methodsmentioning
confidence: 99%